Echocardiographic and signal averaged ECG indices associated with non-sustained ventricular tachycardia after repair of tetralogy of Fallot. Issue 1 (1st January 2001) - Brili, S; Aggeli, C; Gatzoulis, K; Tzonou, A; Hatzos, C; Pitsavos, C; Stefanadis, C; Toutouzas, P
Abstract : OBJECTIVE: To identify any possible association between different readily available non-invasive indices and potential malignant ventricular arrhythmias in patients with repaired tetralogy of Fallot. DESIGN: 27 consecutive patients, mean (SD) age 27.3 (11.7) years, were studied 15.7 (6.7) years after corrective surgery for tetralogy of Fallot, using 12 lead ECG, 24 hour Holter recordings, signal averaged ECG, and echocardiography. The following variables were measured: standard QRS duration, filtered QRS duration (fltQRS), low amplitude signal duration, and root mean square voltage of the last 40 ms of the fltQRS (RMS-40), as well as right ventricular systolic pressure, right ventricular ejection fraction, and the ratio of the maximum short axis diameters of the right and left ventricles (RD:LD). RESULTS: All patients had right bundle branch block, with a mean QRS duration of 137.1 (14.9) ms. There were no patients with sustained arrhythmia. Five patients had runs of non-sustained ventricular tachycardia (group A) and the other 22 patients did not (group B). Univariate analysis showed that fltQRS and RD:LD ratio were significantly associated with non-sustained ventricular tachycardia. In addition, a fltQRS ⩾ 148 ms, low amplitude signal ⩾ 32.5 ms, RMS-40 ⩽ 23 μV, and RD:LD ratio ⩾ 1.05 were cut off points with a high sensitivity for detecting patients with non-sustained ventricular tachycardia. CONCLUSIONS: Abnormal signal averaged ECG and echocardiographic variables are associated with potentially malignant ventricular arrhythmias on the Holter recordings in asymptomatic patients with repaired tetralogy of Fallot.